Functional role of THRAP3 in modulating thyroid hormone–mediated gene networks in C2C12 myotubes - Taku Fukushima; Sachi Kuse; Yuka Hasegawa; Taiju Fujioka; Takeshi Nikawa; Satoru Masubuchi; Iori Sakakibara (PLoS ONE, 2026)
Thyroid hormone (TH) secreted by the thyroid gland plays essential roles in regulating metabolism, development, and nervous system function. Thyroid hormone receptor-associated protein 3 (THRAP3) is a nuclear coactivator that interacts with the thyroid hormone receptor (TR) and facilitates target gene regulation through the mediator complex. Although this mechanism has been well studied in other tissues, the specific role of THRAP3 in skeletal muscle remains unclear. Here we investigated the function of THRAP3 in skeletal muscle using Thrap3 knockout (KO) C2C12 cells. Loss of THRAP3 significantly suppressed the expression of key myogenic regulatory factors, including Myod1 , Mef2c , and myosin heavy chain genes, resulting in impaired myogenic differentiation and muscle diameter. Furthermore, we found that THRAP3 influences triiodothyronine (T3)-induced gene expression, suggesting that it cooperatively modulates thyroid hormone signaling in muscle cells. Taken together, our findings identify THRAP3 as a novel regulator of myogenesis and indicate that it supports T3 activity by coordinating thyroid hormone–responsive gene expression in skeletal muscle.